(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The aim of the study was to evaluate the effectiveness of Calisthenics on self-esteem among elderly. Quantitative research approach, quasi experimental nonequivalent control group pretest posttest design was used to collect the data from 70 elderlies (35 in experimental group and 35 in comparison group) by using convenience sampling technique. The tools used were Sample characteristics performa and Rosenberg’s Self Esteem Scale. For both the groups pre-test, post-test-1and2 were taken on day 1st, 30th and 45th respectively. Calisthenics was given to experimental group thrice a week for four weeks. A significant difference was found in terms of self-esteem between the experimental and comparison group after intervention (t= 17.47 and p=0.001) at 0.05 level of significance. Hence, Calisthenics was found effective in increasing self-esteem among elderly.